PENGARUH PEMAHAMAN SIKLUS AKUNTANSI PERUSAHAAN DAGANG, INTENSITAS LATIHAN SOAL, DAN COMPUTER KNOWLEDGE TERHADAP HASIL BELAJAR KOMPUTER AKUNTANSI DENGAN SELF-EFFICACY SEBAGAI VARIABEL INTERVENING - Manistasari, Suma; Listiadi, Agung (Refleksi Edukatika : Jurnal Ilmiah Kependidikan, 2024)
The aim of this research is to determine the influence of understanding the trading company accounting cycle, intensity of practice questions, and computer knowledge on accounting computer learning outcomes and to investigate the indirect influence through the mediation of the self-efficacy variable in class XI AKL students at SMKN 6 Surabaya.This research is causal associative research with a quantitative approach and data analysis was carried out with the help of the SPSS 25 application. Data analysis carried out included research instrument tests, descriptive statistical tests, classical assumption tests, t tests, coefficient of determination tests, and Sobel tests.The results of this research are that Understanding the Trading Company Accounting Cycle, Intensity of Question Practice, and Computer Knowledge partially influence Accounting Computer Learning Outcomes; Understanding the Trading Company Accounting Cycle, Intensity of Question Practice, and Computer Knowledge also partially influence Self-Efficacy; Understanding the Trading Company Accounting Cycle influences Accounting Computer Learning Outcomes with Self-Efficacy as an Intervening Variable; Question Practice Intensity influences Accounting Computer Learning Outcomes with Self-Efficacy as an Intervening Variable; and Computer Knowledge influences Accounting Computer Learning Outcomes with Self-Efficacy as an Intervening Variable.